2015
DOI: 10.1121/1.4922704
|View full text |Cite
|
Sign up to set email alerts
|

Killer whale call frequency is similar across the oceans, but varies across sympatric ecotypes

Abstract: Killer whale populations may differ in genetics, morphology, ecology, and behavior. In the North Pacific, two sympatric populations ("resident" and "transient") specialize on different prey (fish and marine mammals) and retain reproductive isolation. In the eastern North Atlantic, whales from the same populations have been observed feeding on both fish and marine mammals. Fish-eating North Pacific "residents" are more genetically related to eastern North Atlantic killer whales than to sympatric mammal-eating "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…For example, the calls of North Pacific transient killer whales have overall lower frequencies than North Pacific residents and North Atlantic killer whales (Icelandic and Norwegian populations; Filatova et al, 2015a; Foote & Nystuen, 2008). However, differences between North Pacific residents and North Atlantic killer whales were less pronounced, with significant frequency differences in the low frequency components but no significant differences in the high frequency components (Filatova et al, 2015a). Our results suggest that in the North Atlantic, time and frequency parameters are not clearly distinguishable between locations, at least for killer whales off Iceland and Norway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the calls of North Pacific transient killer whales have overall lower frequencies than North Pacific residents and North Atlantic killer whales (Icelandic and Norwegian populations; Filatova et al, 2015a; Foote & Nystuen, 2008). However, differences between North Pacific residents and North Atlantic killer whales were less pronounced, with significant frequency differences in the low frequency components but no significant differences in the high frequency components (Filatova et al, 2015a). Our results suggest that in the North Atlantic, time and frequency parameters are not clearly distinguishable between locations, at least for killer whales off Iceland and Norway.…”
Section: Discussionmentioning
confidence: 99%
“…A geographic comparison of North Atlantic and North Pacific killer whale sound frequencies was recently published [221].…”
Section: Orcinus Orca-killer Whalementioning
confidence: 99%
“…Studies of the vocal characteristics of different killer whale populations have identified a mix of unique and shared call types and documented 'vocal culture' whereby different killer whale groups exhibit distinct dialects [27][28][29][30]. These dialects are stable through time [31,32] and are a learned behaviour [27,33,34]. Groups with very similar repertoires have been shown to be more closely related than groups that share fewer calls, with some pods of related matrilines sharing many or all of the components in their repertoire [28,35,36].…”
Section: Introductionmentioning
confidence: 99%